Freedom towards tolerance. Tolerance towards freedom - Sztobryn, Sławomir (Granice tolerancji w sztuce i w wychowaniu, 2020)
Tolerance and freedom are conjugate concepts. Freedom is the courage of living according to the order of values. Only a free man is capable of tolerance because it means acknowledging the freedom of another and recognizing his right to be different. I. Lazari-Pawłowska calls this type of tolerance positive. In a partnership, which lies at the basis of tolerance, there is no selfishness or fear, it is not one-sided and carries a positive emotional vibration towards another, yet different person. This understanding of tolerance carries within itself the limitation of one’s freedom in the name of recognizing someone else’s. In T. Kotarbiński’s concept an important component of tolerance is the strength of rationality opposed to thoughtless heftiness. The most common area of tolerance is the sphere of language. The third link in the relation of tolerance and freedom is equality, which is not reduced to exact sameness. Tolerance is the ability – unique for everyone – to accept the difference, it is the ability to be in ambivalence. The concept of a reliable protector by T. Kotarbiński is an expression of a tolerant attitude towards all other living beings.